Peran Keluarga dalam Pembentukan Mental dan Pengaruhnya terhadap Perkembangan Kognitif pada Anak - Nasution, Fauziah; Putri, Junita Hanum Eka; Salsabila, Mutiara; Apriansyah, Andika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to highlight the importance of parental awareness in understanding the growth and development of children. Parents are the first school and teachers are the second education for early childhood. This research is a descriptive qualitative study in the form of a case study. Data was obtained through observations and interviews with parents and teachers. The results of the study show that the role of parents in stimulating children's cognitive development includes: observer, motivator, facilitator, school, and problem solver. Then the impact of parental role on children's cognitive development includes: children are motivated to learn at home, children become more critical, active, experience improvement in achieving better learning outcomes, able to express aspirations, and able to show responsible and confident character.